Hikayat Nakhoda Asik Sapirin bin Usman, Hikayat Merpati Mas Muhammad Bakir - Oman Fathurahman (Manuskripta, 2011)
This review evaluates Henri Chambert-Loir’s critical edition of two 19th-century Batavian Malay manuscripts (Hikayat Nakhoda Asik and Hikayat Merpati Mas) sourced from the Fadli family's commercial lending library in Pecenongan. The reviewer emphasizes the editor's deliberate strategy to popularize classical Malay philology for general readers by prioritizing the narrative stories at the front of the book as entertainment, while placing technical philological apparatuses and critical notes at the back. Structurally, both texts adhere to classic Malay literary tropes involving royal wandering, tests of heroism, and eventual marital and political restoration. A major philological contribution highlighted in the review is Chambert-Loir’s critical verification of authorship (dabt nisbat al-kitāb li-al-mu'allif): despite colophon attestation crediting Muhammad Bakir, textual and linguistic analysis attributes Hikayat Nakhoda Asik to Sapirin bin Usman. Additionally, the review engages with Chambert-Loir's theoretical insights regarding manuscript transcription. It reflects on the inherent limitations of reproducing Malay texts "as close as possible to the original," arguing that transliteration inevitably introduces alterations. The reviewer praises the publication as a highly valuable empirical and methodological benchmark for Nusantara manuscript studies.